The Image of Oppressed Women in the Novel Pada Sebuah Kapal by Nh. Dini - Hona, Theresia Emelia; Dewi, Novita (Universitas Teknokrat Indonesia, 2024)
This research aims to describe the image of oppressed women in the novel Pada Sebuah Kapal by Nh. Dini. The image of women is explained in two forms, namely physical image and psychological image. A woman's physical image and psychological image tend to be the main points of choice. This is due to the development of the times where beauty standards are starting to form in society so that women experience the disadvantages of forming these standards. Beauty standards that apply in society are having an ideal body shape (slim, tall), symmetrical face shape, white skin, straight hair and many more. The method used is descriptive qualitative where quotation data is described and analyzed. Based on this, this research is included in library research and the researcher acts as an instrument. The research data source is the novel Pada Sebuah Kapal. The data in the research is in the form of quotations from sentences, paragraphs and narratives of characters that show the image of women in the novel. The technique used is the reading and writing technique. This means that researchers read the novel first to gain an understanding of the content of the novel. After that, the researcher recorded the quotation data found in the novel Pada Sebuah Kapal. Then, the data is analyzed. The results of the research show that the female characters in the novel experience thoughts of physical and psychological images in the form of complaints, understanding, not being noticed and being compared with other women.Keywords: Novels, oppressed women, physical and psychological images.